(untitled) (University Journal of Zoology, Rajshahi University, 2009)
To establish the indices evaluating the ecological conditions of forests in Bangladesh, total number of butterflies counted in 5 observation sites reached 27,805 (76 species, 10 families). Number of butterflies (IND) and species showed bimodal pattern of seasonal fluctuations peaked in April and November-to- December. The values of I(R5) also showed bimodal seasonal fluctuations peaked in January-to-February and July-to-September. The ratios of IND/I(R5) formed a large peak in November. Results indicate that species diversities of butterflies high in March-to-July decreased thereafter, the numbers of butterflies increased toward November in the study area. Key words: Butterfly, seasonal fluctuation, population indices, ecological states Â doi:10.3329/ujzru.v27i0.1958 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 67-71